Development of an Ethnorealistic Mathematics-Based Electronic Module Integrated with Assemblr 3D in the Context of Lebak Batik to Improve Students' Conceptual Understanding - Andri Imam Subekhi; Nandang Kusmana; Teguh Ardianto; Irvan Fariji; Yusup Junaedi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to develop an Ethno-RME-based e-module integrated with Assemblr 3D in the context of Lebak Batik that is feasible, practical, and effective to improve students' conceptual understanding. This research is included in the research and development referring to the ADDIE development model including the stages of Analysis, Design, Development, Implementation, Evaluation. The testing of the e-module media in learning and testing the ability to understand mathematical concepts was carried out on fifth-grade students at an Elementary School in Banten Province. The trial design of this study used a One Group Pretest-Posttest Design . The results showed that the average percentage of the e-module feasibility score from both validators was 87% with very feasible criteria. The use of the e-module in the limited trial obtained an average score from teachers and students of 75.2% with practical criteria. Ethno-RME-based e-module integrated with Assemblr 3D in the context of Lebak Batik effective in improving students' understanding of mathematical concepts, as indicated by a difference in conceptual understanding test results from 40 to 86.5 with an N-Gain score of 0.77 in the high category. These results indicate that the e-module The developed materials have the criteria of being feasible, practical and effective in improving students' understanding of concepts